Delayed initiation of breastfeeding in Bukavu, South Kivu, eastern Democratic Republic of the Congo: a cross-sectional study - Richard Mbusa Kambale; Jérémie Bisimwa Buliga; Nancy Francisca Isia; Adolphe Nyakasane Muhimuzi; Oreste Battisti; Bruno Masumbuko Mungo (BMC, 2018)
Abstract Background Timely initiation of breastfeeding can decrease neonatal mortality. However, about 50% of newborns are not breastfeed within 1 h of birth in the Democratic Republic of Congo. The aim of this study was to identify factors associated with delayed initiation of breastfeeding in an urban and rural area of Bukavu, South Kivu province, Democratic Republic of Congo. Methods We interviewed 396 mother-newborn pairs (185 in the urban area and 211 in the rural area) between 20 July and 10 October 2016. We used descriptive statistics to demonstrate the prevalence of early initiation of breastfeeding. Variables that showed association with delayed initiation of breastfeeding in the bivariate models were entered in a multivariable logistic model. Results Overall, the rate of early initiation of breastfeeding was 65.9% (69.7% in the rural area, 61.6% in the rural area). Two hundred and seventy-four (62.9%) mothers (159 in rural area and 115 in urban area) were counselled on early initiation of breastfeeding during prenatal care. Most mothers, 65.2% received counselling by a health professional. On multivariable regression analyses after adjusting for other variables in the model, unmarried mothers [Odds Ratio (OR): 1.5 (95% Confidence Interval (CI): 1.13, 1.95)], cesarean delivery [OR: 2.24 (95% CI: 1.74, 2.88)], no counselling on timely initiation of breastfeeding [OR: 1.71 (95% CI: 1.29, 2.20)] and counselling by a non-health professional [OR: 1.84 (95% CI: 1.08, 3.12)] were associated with delayed initiation of breastfeeding. Conclusion Systemic changes are needed for women having caesarean births to experience skin-to-skin and early initiation. In addition, information, education and communication on the importance of timely initiation of breastfeeding must be supported to improve maternal and infant wellbeing.